Analyzing the Reliability of a Pumping System through the Application of Copula Analysis - Elsayed Elshoubary; Taha Radwan (International Journal of Mathematics and Mathematical Sciences)
This paper derives and evaluates the reliability measures for a model pumping system composed of six subsystems linked in series: subsystems 1, 2, and 6, each comprising one unit, while subsystems 3 and 5 each contain three units operating in parallel. Subsystem 4 contains three units effectively operating in series. Unit failure rates are assumed to be constant, while repair rates are modeled by either a general distribution or, in the event of system failure, a Gumbel–Hougaard copula. The Laplace transform and additional supplementary variable approaches are employed to solve the system. The conventional measures of reliability are computed for a range of parameter values and as functions of time. In addition, tables are presented containing parameters for different cases, accompanied by a discussion of how they were chosen and their impact on the results.